Analisis Efisiensi Teknis Dana Kapitasi Puskesmas di Kabupaten Sleman Menggunakan Data Envelopment Analysis - Mas’ud Mas’ud; Laksono Trisnantoro; Julita Hendrartini (Center for Health Policy and Management, 2016)
ABSTRACTBackground. Presidential Decree No. 12/2013 states that BPJS Health in carrying out health insurance, using a capitation financing system in health care first level (primary). According to Minister Regulation No.19 / 2014, that the allocation of capitation funds used for the payment of health care services for health workers and non-health workers who perform services on health care first level. While the operational services allocated for drugs, medical devices, and medical consumable material and other health care operations. Necessary to study the use of the funds in question so that the operational and health services can run effectively, efficiently in order to determine the appropriate policies by local government and center.Methods. This type of study is a mixed analytic methods. In the quantitative data analysis method Data Envelopment Analysis (DEA) and qualitative data to explain the quantitative data. The study population includes all government-owned health centers in Sleman (25 health centers. This study will look at the efficiency of technical management puskesmas capitation funds for the implementation of individual health efforts in Sleman district PHC in 2014.Results. Based on the analysis with DEA method, only 3 of the 25 health centers health centers (12%) which has been technically cost efficiency and 13 health centers (52%) were technically efficient system. Tobit regression analysis shows that there are four variables that significantly, variable utilization figure (positive direction), reference number (positive direction), the ratio of non-medical personnel (negative direction), and capitation funds (negative direction).Conclusion and Suggestions. In general, health centers in Sleman yet technically efficient in the management of capitation funds. Policy-oriented technical efficiency costs will affect the value of the technical efficiency of the system. Expected DHO monitoring, evaluation and improvement of the efficiency of the management of Puskesmas capitation funds intensively and comprehensively on the quality of the performance of health centers as an indicator.Keywords. Capitation Funding, Primary Health Care, Technical Efficiency, Data Envelopment Analysis (DEA).ABSTRAKLatar Belakang. Perpres No. 12/2013 menyebutkan bahwa BPJS Kesehatan dalam menyelenggarakan jaminan kesehatan, menggunakan sistem pembiayaan kapitasi di faskes tingkat pertama (primer). Menurut Permenkes No.19/2014, bahwa alokasi dana kapitasi dipergunakan untuk pembayaran jasa pelayanan kesehatan bagi tenaga kesehatan dan tenaga non kesehatan yang melakukan pelayanan pada FKTP (60%). Sedangkan layanan operasional dialokasikan untuk obat, alat kesehatan, dan bahan medis habis pakai dan kegiatan operasional pelayanan kesehatan lainnya. Diperlukan kajian penggunaan dana yang dimaksud sehingga operasional dan layanan kesehatan dapat berjalan efektif, efisien guna menentukan kebijakan yang tepat oleh pemdah dan pusat.Metode. Jenis Penelitian ini merupakan analitik dengan pendekatan mixed methods. Pada data kuantitatif menggunakan metode analisis Data Envelopment Analysis (DEA) dan data kualitatif menjelaskan data kuantitatif. Populasi penelitian meliputi seluruh puskesmas milik pemerintah di Kabupaten Sleman (25 puskesmas). Penelitian ini akan melihat efisiensi secara teknis pengelolaan dana kapitasi puskesmas terhadap penyelenggaraan upaya kesehatan perorangan di puskesmas Kabupaten Sleman tahun 2014.Hasil. Berdasarkan hasil analisis dengan metode DEA, dari 25 puskesmas hanya 3 puskesmas (12%) yang telah efisiensi secara teknis biaya dan 13 puskesmas (52%) yang efisien secara teknis sistem. Hasil analisis regresi tobit menunjukkan terdapat 4 variabel yang berpengaruh secara signifikan, yaitu variabel angka utilisasi (arah positif), angka rujukan (arah positif), rasio tenaga non kesehatan(arah negatif), dan dana kapitasi (arah negatif).Kesimpulan dan Saran. Secara umum puskesmas di Kabupaten Sleman belum efisien secara teknis dalam pengelolaan dana kapitasi. Kebijakan yang berorientasi kepada efisiensi teknis biaya akan berpengaruh terhadap nilai efisiensi teknis sistem. Diharapkan Dinkes melakukan monitoring, evaluasi serta peningkatan efisiensi pengelolaan dana kapitasi puskesmas secara intensif dan komprehensif terhadap mutu kinerja puskesmas sebagai indikatornya.Kata Kunci. Dana Kapitasi, Puskesmas, Efisiensi Teknis, Data Envelopment Analysis (DEA).